Honduras's Growth Performance During 1970-1997 - Juan-Ramon, V. (IMF Policy Discussion Papers; Policy Discussion Paper, 1999)
For more than three decades, Honduras's average annual growth in real per capita GDP has been almost zero and highly uneven, even though its total investment-to-GDP ratio has been relatively large. This paper argues that policy and efficiency variables seem to have had less of an influence on growth in Honduras than they had on other countries. Instead, lack of growth can be attributed to the offsetting negative influence of low labor and capital productivity, which result from deficient levels of human capital and inadequate composition of investment. Other constraints to growth in Honduras include inadequate physical and institutional infrastructures.